PENGARUH PIUTANG USAHA TERHADAP RENTABILITAS PADA PERUSAHAAN MANUFAKTUR YANG ADA DI BURSA EFEK INDONESIA - Butarbutar, Ribka Sari; Khairani, Rafida; Wijaya, Noviyanti (Fakultas Ekonomi Prodi Akuntansi, 2022)
This research aims to influence business credit on profitability in manufacturing companies on the Indonesian stock exchange. The population in this study is the financial reports of manufacturing companies operating in the food and beverage sector that were registered on the IDX starting from 2008-2011, totaling 16 companies. The sample in this research is the financial reports of manufacturing companies operating in the food and beverage sector that were registered on the IDX starting from 2008-2011, totaling 10 companies. The data collection method used in this research is documentation by collecting secondary data in the form of published financial reports of food and beverage companies and these companies are listed on the Indonesia Stock Exchange (BEI). The data used in this research was obtained from the Indonesian Capital Market Directory (ICMD) and downloaded via the website www.idx.co.id. The results of the research show (1) by calculating Simple Linear Regression, the constant value equation (a) is 3.405, while the regression coefficient value (b) is -0.139, so the Simple Linear Regression equation obtained is Y=3.405+(-0.139X). (2) Business credit has no significant effect on profitability at 0.547. (3) The determinant coefficient (R2) is 0.010. This means that 1% of variations or changes in profitability can be explained by variations or changes in trade receivables while the remaining 99% is explained by other factors not included in this research.